Effect of Integrated Use of Nitrogen on Yield and Nutrient Uptake of Summer Onion - Sultana, Saima; Paul, Alok Kumar; Sultana, Deeder; Fazle Bari, A. S. M. (International Journal of Bio-resource and Stress Management, 2023)
Effect of integrated use of nitrogen on yield and nutrient uptake of summer onion (Allium cepa var. BARI Piaz-2) was assessed in a field experiment carried out in Sher-e-Bangla Agricultural University Farm, Dhaka during the kharif season of 2007. Urea, cowdung (CD) and vermicompost (VC) were combined in a way to supply N at 120 kg ha-1 from the sources and set in twelve treatments such no fertilizer (T1), 120 kg N ha-1 supplied from urea (T2), 100 kg N ha-1 supplied from urea with 20 kg from CD (T3), 100 kg N ha-1 supplied from urea with 20 kg from VC (T4), 80 kg N ha-1 supplied from urea with 40 kg from CD (T5), 80 kg N ha-1 supplied from urea with 40 kg from VC (T6), 60 kg N ha-1 supplied from urea with 60 kg from CD (T7), 60 kg N ha-1 supplied from urea with 60 kg from VC (T8), 40 kg N ha-1 supplied from urea with 80 kg from CD (T9), 40 kg N ha-1 supplied from urea with 80 kg from VC (T10), 120 kg N ha-1 supplied from CD (T11), 120 kg N ha-1 supplied from VC (T12), arranged in a RCBD design with three replications. The results indicated that maximum bulb yield (12.16 t ha-1) and stover yield (5.46 t ha-1) of summer onion were obtained in treatment receiving 80 kg N ha-1 from urea with 40 kg N ha-1 substituted by CD (T5), followed by the treatment receiving 80 kg N ha-1 from urea with 40 kg N ha-1 substituted by VC (T6). Comparing with other fertilizer treatments, the yields were significantly lower in treatments where N from urea source was below 50%. Similarly, the N, P, K and S uptake (72.78, 5.53, 55.88 and 28.93 kg ha-1, respectively) by onion plants at harvest stage was also significantly (p<0.01) greater in treatments receiving 80 kg N ha-1 from urea with 40 kg from CD (T5) followed by treatment T6. Thus the data suggest that integrated use of N 80 kg from urea with 40 kg from CD or 80 kg from urea with 40 kg from VC has produced maximum yields and is therefore recommended for advantageous onion production.